2015
DOI: 10.1038/leu.2015.124
|View full text |Cite
|
Sign up to set email alerts
|

Selective targeting of IRF4 by synthetic microRNA-125b-5p mimics induces anti-multiple myeloma activity in vitro and in vivo

Abstract: Interferon regulatory factor 4 (IRF4) is an attractive therapeutic target in multiple myeloma (MM). We here report that expression of IRF4 mRNA inversely correlates with microRNA (miR)-125b in MM patients. Moreover, we provide evidence that miR-125b is downregulated in TC2/3 molecular MM subgroups and in established cell lines. Importantly, constitutive expression of miR-125b-5p by lentiviral vectors or transfection with synthetic mimics impaired growth and survival of MM cells and overcame the protective role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 52 publications
5
86
1
Order By: Relevance
“…We then validated the elevated levels of five of those (miR-125b-5p, miR-4326, miR-4498, miR-490-3p and miR-7155-5p) in a second clinical study. Most of the targets of these miRNAs are cancer-associated genes such as APC2, IGF2, and IRF4 (15)(16)(17) that are involved in cell proliferation, cell cycle, apoptosis, invasion and metastasis. Fur ther more, ROC analysis demonstrated that miR-125b-5p and miR-490-3p were accurate in distinguishing MM patients from healthy subjects, resulting in AUCs of 0.954 (sensitivity=86%, specificity=96%, 95% CI 0.901-1.006, P<0.001) and 0.866 (sensitivity=60%, specificity=85%, 95% CI 0.522-0.836, P= 0.028), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We then validated the elevated levels of five of those (miR-125b-5p, miR-4326, miR-4498, miR-490-3p and miR-7155-5p) in a second clinical study. Most of the targets of these miRNAs are cancer-associated genes such as APC2, IGF2, and IRF4 (15)(16)(17) that are involved in cell proliferation, cell cycle, apoptosis, invasion and metastasis. Fur ther more, ROC analysis demonstrated that miR-125b-5p and miR-490-3p were accurate in distinguishing MM patients from healthy subjects, resulting in AUCs of 0.954 (sensitivity=86%, specificity=96%, 95% CI 0.901-1.006, P<0.001) and 0.866 (sensitivity=60%, specificity=85%, 95% CI 0.522-0.836, P= 0.028), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Because IRF4 is a well-characterized myeloma survival factor, 28,29 we investigated whether IRF4 levels changed in cells that were overexpressing either the CD86FLm or CD86TLm constructs. We found that overexpression of CD86FLm led to a modest increase in IRF4 at both the mRNA and protein levels ( Figure 5C-D).…”
Section: Cytoplasmic Tail Of Cd86 Plays a Role In Cd28-cd86 Functionmentioning
confidence: 99%
“…miR-125b could also protect the ethanol-induced apoptosis and embryotoxicity (35). Due to incomplete binding with the 3'-untranslated region of target mRNA, miR-125b may serve various roles in different diseases or processes (36,37). miRNA may regulate different genes and serve different functions.…”
Section: Discussionmentioning
confidence: 99%